Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I have a task which I do not understand:

Consider $w = \frac{z}{z^2+1}$ where $z = x + iy$, $y \not= 0$ and $z^2 + 1 \not= 0$.

Given that Im $w = 0$, show that $| z | = 1$.

Partial solution (thanks to @ABC and @aranya):

If I substitute $z$ with $x + iy$ then we have $w = \frac{x + iy}{x^2+2xyi-y^2+1}$ or written slightly different $w= \frac{x + iy}{x^2-y^2+1+2xyi}$ or $w= \frac{x + iy}{(x^2-y^2+1)+(2xyi)}$.

In this format we can multiply with complex conjugate $w= \frac{x + iy}{(x^2-y^2+1)+(2xyi)}\cdot\frac{(x^2-y^2+1)-(2xyi)}{(x^2-y^2+1)-(2xyi)}$.

Then we get $w=\frac{x^3+xy^2-x^2yi-y^3i+x+iy}{(x^2+^2+1)^2-(2xyi)^2} = \frac{(x^3+xy^2+x)+(-x^2yi-y^3i+iy)}{(x^2+^2+1)^2+(2xy)^2} = \frac{(x^3+xy^2+x)+i(-x^2y-y^3+y)}{(x^2+^2+1)^2+(2xy)^2}$.

And as stated above, imaginary part of $w = 0$ meaning $\frac{-x^2y-y^3+y}{(x^2+^2+1)^2+(2xy)^2} = 0$.

As denominator can't be zero, means nominator is zero $-x^2y-y^3+y=0$. Or $y\cdot(-x^2-y^2+1)=0$. As $y\not=0$ implies $-x^2-y^2+1=0$ or $x^2+y^2=1$.

What now?

share|cite|improve this question
You have a relation $w=\frac{z}{z^2+1}$ that for each number $z$ gives you a number $w$. You are supposed to assume that the imaginary part of $w$ is zero, i.e. $w$ is a real number. You have to show that the number $z$ you put in the right hand side has absolute value equal to one. – Mlazhinka Shung Gronzalez LeWy Nov 11 '13 at 19:33
hint: if we expand using x and y and then multiply by complex conjugate of the denominator then what do we get? – Aranya Lahiri Nov 11 '13 at 19:33

$$w=\frac z{z^2+1}=\frac{|z|^2\overline z+z}{|z^2+1|^2}$$

and thus

$$\text{Im}\,w=0\iff \text{Im}\,z\cdot\left(|z|^2-1\right)=0\stackrel{\text{since Im}\,z=y\neq 0}\iff |z|^2=1\;\ldots$$

share|cite|improve this answer
I just started learning complex numbers and I do not fully follow you. – Anja_7 Nov 11 '13 at 20:29
@Anja_7, you just need to be sure you know or can prove that $$\forall\,z=x+iy\in\Bbb C\;\;,\;\;z\overline z=|z|^2\;,\;\;|z|^2\overline z+z=|z|^2(x-iy)+x+iy$$and thus the imaginary part of $\;w\;$ is what is written in the answer above. – DonAntonio Nov 11 '13 at 20:40

You're basically done, since $x^2+y^2=\left|z\right|^2$.

share|cite|improve this answer

Saying that the imaginary part of $w$ is zero means $w=\bar{w}$, so $$ \frac{z}{z^2+1}=\frac{\bar{z}}{\bar{z}^2+1} $$ and therefore $$ z\bar{z}^2+z=z^2\bar{z}+\bar{z}. $$ This can be rewritten as $$ z-\bar{z}=z^2\bar{z}-z\bar{z}^2 $$ and, collecting $z\bar{z}$ in the left-hand side, $$ z-\bar{z}=z\bar{z}(z-\bar{z}). $$ The hypothesis $y\ne0$ means $z\ne\bar{z}$ and so we get $$ 1=z\bar{z}, $$ that is, $|z|^2=1$.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.